Cardiovascular magnetic resonance-guided right heart catheterization in a conventional CMR environment – predictors of procedure success and duration in pulmonary artery hypertension - Daniel S. Knight; Tushar Kotecha; Ana Martinez-Naharro; James T. Brown; Michele Bertelli; Marianna Fontana; Vivek Muthurangu; J. Gerry Coghlan (Journal of Cardiovascular Magnetic Resonance, 2019)
Abstract Background Cardiovascular magnetic resonance imaging (CMR) is valuable for the investigation and management of pulmonary artery hypertension (PAH), but the direct measurement of pulmonary hemodynamics by right heart catheterization is still necessary. CMR-guided right heart catheterization (CMR-RHC) combines the benefits of CMR and invasive cardiac catheterization, but its feasibility in patients with acquired PAH has not been established. The aims of this study are to: (1) demonstrate the feasibility of CMR-RHC in patients being assessed for PAH in a conventional diagnostic CMR scanner room; (2) determine the predictors of (i) procedure duration, and (ii) procedural failure or technical difficulty as determined by the adjunctive need for a guidewire. Methods Fifty patients investigated for suspected or known PH underwent CMR-RHC. Durations of separate procedural components were recorded, including time taken to pass the catheter from the femoral vein to a stable wedge position (procedure time) and total time the patient spent in the CMR department (department time). Associations between procedural failure/guidewire usage and hemodynamic/CMR measures were assessed using logistic regression. Relationships between procedure times and hemodynamic/CMR measures were evaluated using Spearman’s correlation coefficient. Results A full CMR-RHC study was successfully completed in 47 (94%) patients. CMR-conditional guidewires were used in 6 (12%) patients. Metrics associated with guidewire use/procedural failure were higher mean pulmonary artery (PA) pressures (mPAP: OR = 1.125, p = 0.018), right heart dilatation (right ventricular (RV) end-systolic volume (RVESV): OR = 1.028, p = 0.018), RV hypertrophy (OR = 1.050, p = 0.0067) and RV ejection fraction (EF) (OR = 0.914, p = 0.014). Median catheter and department times were 3.6 (2.0–7.7) minutes and 60.0 (54.0–68.5) minutes, respectively. All procedure times became significantly shorter with increasing procedural experience (p < 0.05). Catheterization time was also associated with PH severity (RV systolic pressure: rho = 0.46, p = 0.0013) and increasing RV end-systolic volume (RVESV: rho = 0.41, p = 0.0043), hypertrophy (rho = 0.43, p = 0.0025) and dysfunction (RVEF: rho = − 0.32, p = 0.031). Conclusions This study demonstrates that CMR-RHC using standard technology can be incorporated into routine clinical practice for the investigation of PAH. Procedural failure was rare but more likely in patients with severe PAH. Procedure time is clinically acceptable and increases with worsening PAH severity.